Redesigning the Signage System of Abhirama Park Sidoarjo - Kurniasari, Novia; Fitria, Yassinta; Suminar, Adinda Diayu Cahaya; Setiawan, Teofilus Kharisma Bagus; Pratama, Abyan Dhia; Widyasari, Widyasari (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Abhirama Park, a green open space in Sidoarjo, is directly managed by the Environmental and Sanitation Agency (DLHK) of Sidoarjo Regency. The park’s primary attraction lies in its playground facilities and recreational areas, making it a popular destination for children and families. Beyond its recreational value, Abhirama Park also serves as an educational space for children, promoting environmental cleanliness. The park offers an interactive experience for visitors, allowing them to engage with animals such as birds, chickens, and fish. While some signage is already present, it is deemed insufficient in effectively conveying information to visitors. The presence of signage is crucial for facilitating navigation, particularly for first-time visitors to a tourist destination. Therefore, this study aims to redesign the signage system to enhance its informativeness, aesthetics, and functionality, meeting the specific needs of visitors. The research methodology employed is a collaborative approach that integrates design principles with the TOWS matrix analysis technique. This approach ensures that the signage design aligns with the park’s identity and appeals to the target audience. The resulting signage design strategically positions information to enhance the overall experience and satisfaction of visitors during their visit.